A Phase I Study of a Combination of Yttrium-90 labeled Anti-CEA Antibody and Gemcitabine in Patients with CEA Producing Advanced Malignancies - Shibata, Stephen (2009)
PURPOSE: To determine the maximum tolerated dose of combined therapy using an yttrium-90 labeled anti-CEA antibody with gemcitabine in patients with advanced CEA producing solid tumors. EXPERIMENTAL DESIGN: The chimeric human/murine cT84.66 is an anti-CEA intact IgG1, with high affinity and specificity to CEA. This was given at a fixed yttrium-90 labeled dose of 16.6 mCi/m(2) to subjects who had and an elevated CEA in serum or in tumor by immunohistochemistry. Also required was a tumor that imaged with an (111)In labeled cT84.66 antibody. Patients were treated with escalating doses of gemcitabine given intravenously over 30 minutes on day 1 and 3 after the infusion of the yttrium-90 labeled antibody. Patients were treated in cohorts of 3. The maximum tolerated dose was determined as the highest level at which no more than 1 of 6 patients experienced a dose limiting toxicity. RESULTS: A total of 36 patients were enrolled, and all but one had prior systemic therapy. The maximum tolerated dose of gemcitabine in this combination was 150mg/m(2). Dose limiting toxicities at a gemcitabine dose of 165mg/m(2) included a grade 3 rash and grade 4 neutropenia. One partial response was seen in a patient with colorectal cancer, and 4 patients had a > 50% decrease in baseline CEA levels associated with stable disease. Human antichimeric antibody responses were the primary reason for stopping treatment in 12 patients. CONCLUSIONS: feasibility of combining gemcitabine with an yttrium-90 labeled anti-CEA antibody is demonstrated with preliminary evidence of clinical response.